HUBUNGAN ANTARA KEKUATAN MENGGENGGAM DENGAN GAIT SPEED PADA LANSIA - Ismawati Nur Azizyah (2022)
The aging process results in several changes in body systems, one of which is muscle weakness. Muscle weakness affects almost all daily activities and can lead to functional decline in the elderly. in the end, reduced functional capacity can cause parents to become dependent on others. The purpose of this study was to determine the relationship between grip strength and gait speed in the elderly. This study uses a descriptive correlation research with cross sectional examples. The measuring instrument used to measure grip strength is the Hand Grip Dynamometer and to measure the gait speed is the 10 Meter Walking Test, and the sample size is 35 elderly people in the Dahlia Senja Community. The data analysis used is univariate and bivariate analysis. The results of research that has been carried out using the Spearman Rho correlation test method can be concluded that there is no relationship between grip strength and gait speed in the elderly. The conclusion is suggested with a larger number of samples and a more precise research screening, to be able to find a wider range of respondents' characteristics which are expected to be wider.